2013
DOI: 10.1051/orthodfr/2013049
|View full text |Cite
|
Sign up to set email alerts
|

Relation entre la chirurgie orthognatique et les dysfonctionnements de l’appareil manducateur. Revue de la littérature

Abstract: Les dysfonctionnements de l’appareil manducateur (DAM) correspondent aux douleurs et aux troubles du fonctionnement de l’appareil manducateur en rapport avec une anomalie musculo-squelettique. Le caractère multifactoriel des étiologies est maintenant reconnu. Parmi les étiologies, le rôle de la chirurgie orthodontique est encore discuté. L’analyse de la littérature de 2000 à 2011 révèle, pour la plupart des auteurs, une diminution de la fréquence et de l’intensité des signes cliniques après la chirurgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Once the research question had been formulated, the definition of PICOS ( [15]), that evaluate the prevalence of TMDs during orthodontic-surgical treatment. TMD is diagnosed using the "diagnostic criteria for temporomandibular disorders (DC/TMDs)" diagnostic algorithm and/or, for disc displacements, magnetic resonance imaging (MRI).…”
Section: Research Question and Eligibility Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Once the research question had been formulated, the definition of PICOS ( [15]), that evaluate the prevalence of TMDs during orthodontic-surgical treatment. TMD is diagnosed using the "diagnostic criteria for temporomandibular disorders (DC/TMDs)" diagnostic algorithm and/or, for disc displacements, magnetic resonance imaging (MRI).…”
Section: Research Question and Eligibility Criteriamentioning
confidence: 99%
“…In 2009, Al-Riyami et al [14] carried out a systematic review of the literature and concluded that although orthognathic surgery should not be recommended solely for the treatment of TMD, patients who receive orthodontic-surgical treatment and who also suffer from TMD appear to more likely see an improvement in their signs and symptoms than a deterioration. In 2013, Chauvel-Lebret et al [15], in a systematic review on the subject, concluded that surgery had a variable and unpredictable effect on TMD. In 2017, Al-Moraissi et al [16] conducted a systematic review and meta-analysis (including 29 studies and 5029 patients) with follow-up periods varying from 4 months to 6.3 years, and concluded that orthognathic surgery reduced TMD symptoms in many patients who had symptoms before surgery, but created symptoms in a smaller group of patients who were asymptomatic before surgery.…”
Section: Introductionmentioning
confidence: 99%